Decoding the implications of subcellular h2o2 dynamics in a stroke-on-a-dish model using cerebral microvascular endothelial cells - Kalkan Yazıcı, Merve; Kekeç, Enes Görkem; Üvak, Melike Tuğba; Eroğlu, Emrah (My University, 2024)
[Abstract Not Available]
Keywords: Biochemistry; Molecular Biology; Endocrinology; Metabolism